PERBANDINGAN PENGGUNAAN DINDING PENAHAN TANAH TIPE KANTILEVER DAN GRAVITASI DENGAN VARIASI KETINGGIAN LERENG GUNUNG LIO SALEM KABUPATEN BREBES - Diantoro, Wahudin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Efforts to improve slope stability have several methods that can be used, one of which is to use retaining wall construction. A retaining wall is a construction that functions to withstand lateral earth pressure generated by the soil behind the retaining wall. There are two types of retaining walls that are often found in the field, namely the gravity type and the cantilever type. This study aims to compare the use of the two types of retaining walls at various slope heights. The soil data used in this study is soil data at the Lio Salem Slope BTN location, Brebes Regency. The results showed that at a slope height of up to 7 m, the safety or stability value for the cantilever type was higher than for the gravity type, both for stability against bearing capacity collapse, overturning, and shearing.